2013
DOI: 10.1186/2193-1801-2-28
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the stem bark of Shorea roxburghii and its silver reducing power

Abstract: A detailed study has been performed on the antioxidant activity of the acetone and methanol extracts of the stem bark of the plant, Shorea roxburghii. The total phenolic content and antioxidant activity of the extracts were determined by DPPH, radical scavenging, ferric ion reducing power, hydroxyl radical, ABTS. radical scavenging and hydrogen peroxide scavenging activities. Reducing efficiency of the S. roxburghii towards silver nanoparticles has been evaluated using surface plasmon resonance and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 62 publications
(60 reference statements)
4
43
0
Order By: Relevance
“…The 50% inhibition of AIAgNPs and AILE was observed at 30 and 40 g/mL concentration respectively. Our observations are good accordance with an earlier report on the H 2 O 2 scavenging effect of stem bark extract of Shorea roxburghii [42].…”
Section: Antioxidant Potentialsupporting
confidence: 95%
“…The 50% inhibition of AIAgNPs and AILE was observed at 30 and 40 g/mL concentration respectively. Our observations are good accordance with an earlier report on the H 2 O 2 scavenging effect of stem bark extract of Shorea roxburghii [42].…”
Section: Antioxidant Potentialsupporting
confidence: 95%
“…ZnO NPs synthesized by O. tenuiflorum act as potential antioxidants [49]. Nanoparticles of gold [50], silver [51], selenium [52] and copper oxide [53] are known to exhibit free radical scavenging activity. Thus, the antioxidant activity of ZnO NPs may be attributed to the functional group adhered.…”
Section: Antioxidant Activity Of Zno Nanoparticlesmentioning
confidence: 99%
“…Subramanian et al demonstrated that the stem bark extract of Shorea roxburghii contain high level of total phenolic compounds and radical scavenging activity. They also revealed that the plant extract could be used as an efficient green reducing agent for the production of SNPs [27]. Ahmad et al reported that the phenolic compounds in pineapple, exhibit excellent antioxidant activity and these phenols can react with a free radical to form the phenoxy radicals.…”
Section: Dpph Scavenging Assaymentioning
confidence: 99%